Teachers' professional digital competence: an overview of conceptualisations in the literature - Skantz-Åberg, Ewa; Lantz-Andersson, Annika; Lundin, Mona; Williams, Pia (Cogent education, 2022)
Educational research has increasingly drawn attention to teachers' professional digital competence.Various theoretical and methodological perspectives involving a plethora of terms are used to investigate teachers' competences in relation to technology-based teaching. The concept of teachers' professional digital competence still appears to be ambiguous and elusive. This literature overview aims to scrutinise if, and how the concepts addressing teachers' professional digital competence are defined or conceptualised in research. In the publications retrieved from the search in educational databases, we found that the concept of teachers' professional digital competence, or related concepts, was frequently mentioned in abstracts, keywords and full texts, but to a large extent, it was rarely described in detail. In our final corpus of 18 publications, we could distinguish seven recurring aspects of teachers' professional digital competence; 1) technological competence, 2) content knowledge, 3) attitudes to technology use, 4) pedagogical competence, 5) cultural awareness, 6) critical approach and 7) professional engagement, with the technological and pedagogical competences as the most prominent. Inspired by Bronfenbrenner's ecological systems theory, these aspects are analysed as operating within microsystems of individual teachers and within meso- and macrosystems of interactive teachers in interplay with the situated classroom contexts and on larger societal systems.